Cross‐sectional associations of objectively measured physical activity, cardiorespiratory fitness and anthropometry in european adults. (13th August 2013) - Wientzek, Angelika; Tormo Díaz, María‐José; Castaño, Jose Maria Huerta; Amiano, Pilar; Arriola, Larraitz; Overvad, Kim; Østergaard, Jane Nautrup; Charles, Marie‐Aline; Fagherazzi, Guy; Palli, Domenico; Bendinelli, Benedetta; Skeie, Guri; et al.
<x xml:space="preserve">Abstract</x> Objective To quantify the independent associations between objectively measured physical activity (PA), cardiorespiratory fitness (CRF), and anthropometry in European men and women. Methods 2, 056 volunteers from 12 centers across Europe were fitted with a heart rate and movement sensor at 2 visits 4 months apart for a total of 8 days. CRF (ml/kg/min) was estimated from an 8 minute ramped step test. A cross‐sectional analysis of the independent associations between objectively measured PA (m/s2/d), moderate and vigorous physical activity (MVPA) (%time/d), sedentary time (%time/d), CRF, and anthropometry using sex stratified multiple linear regression was performed. Results In mutually adjusted models, CRF, PA, and MVPA were inversely associated with all anthropometric markers in women. In men, CRF, PA, and MVPA were inversely associated with BMI, whereas only CRF was significantly associated with the other anthropometric markers. Sedentary time was positively associated with all anthropometric markers, however, after adjustment for CRF significant in women only. Conclusion CRF, PA, MVPA, and sedentary time are differently associated with anthropometric markers in men and women. CRF appears to attenuate associations between PA, MVPA, and sedentary time. These observations may have implications for prevention of obesity.